2004
DOI: 10.1093/jac/dkh218
|View full text |Cite
|
Sign up to set email alerts
|

In vitro susceptibility of recent antibiotic-resistant urinary pathogens to ertapenem and 12 other antibiotics

Abstract: In view of its significant antibiotic potency against antibiotic-resistant Enterobacteriaceae, ertapenem may constitute a good therapeutic alternative in urinary infections caused by these pathogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
26
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 12 publications
7
26
0
1
Order By: Relevance
“…Antibiotic resistance has also been a concern in Canada and internationally (7)(8)(9)(10)(11)(12)(13). Escherichia coli, the most prevalent urinary tract pathogen, has shown high resistance to commonly used antibiotics, such as amoxicillin and trimethoprimsulfamethoxazole (14)(15)(16)(17).…”
mentioning
confidence: 99%
“…Antibiotic resistance has also been a concern in Canada and internationally (7)(8)(9)(10)(11)(12)(13). Escherichia coli, the most prevalent urinary tract pathogen, has shown high resistance to commonly used antibiotics, such as amoxicillin and trimethoprimsulfamethoxazole (14)(15)(16)(17).…”
mentioning
confidence: 99%
“…Carbapenems, such as imipenem and meropenem, are commonly used for the treatment of ESBL-positive and Gram-negative bacterial infections (1,3,18). Resistance rates of carbapenems have been reported between 0-11.1% (1,18). In our study, although no resistance was observed against imipenem and meropenem in E. coli and K. pneumoniae strains, the resistance rate of ertapenem was assessed as 1.9% and 3.8%, respectively.…”
Section: Discussionmentioning
confidence: 51%
“…In our study, although no resistance was observed against imipenem and meropenem in E. coli and K. pneumoniae strains, the resistance rate of ertapenem was assessed as 1.9% and 3.8%, respectively. Amikacin is the second most active antibiotic following Carbapenems (12,18). In our study, the resistance rates of Amikacin in ESBL-positive E. coli and K. pneumoniae strains were 13.2% and 3.8%, respectively.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…18,32 These issues have led to restricted therapeutic use of fosfomycin as a single agent. However, at the present time, when there is a shortage of antibiotic research and a dramatic development of antimicrobial resistance, [33][34][35][36][37][38][39][40][41][42] previous prescribing habits must be reconsidered and better use made of the old antimicrobial agents, like fosfomycin.…”
Section: Pharmacokinetics and Pharmacodynamics Descriptionmentioning
confidence: 99%